The role of social media in information dissemination to improve youth interactions - Priscilla Kwekie Tetteh; Philip Kwaku Kankam (Cogent Social Sciences, 2024)
This study investigated how youth in Community 8 in Tema, Ghana, used social media and how that affected their interpersonal and communication skills. The study used a combined framework of the Social Learning Theory and Media Richness Theory, as well as an exploratory descriptive design and a qualitative technique, to investigate how youth in Ghana’s Tema Community 8 perceive and use media. Thematic analysis was used to identify the main themes and patterns in the data acquired from a sample of 16 youths between the ages of 15 and 25 using semi-structured interviews, focus groups, and observation. Based on the findings of the study, for young people, social media is the preferred method of contact over face-to-face encounters. Some individuals believed that a more deliberate balance between digital and bodily interactions was necessary. When it comes to effects on the ability to communicate face-to-face, there is a reduction in abilities but some apparent advances in expressiveness. Comparing platforms, advantages included increased networks and innovation, but overuse led to social anxiety and distraction. The study demonstrates the need for parental mediation, digital literacy programs that enable youth to use technology intentionally and responsibly, partnerships between legislators, policymakers, and technology companies, and guidance and interventions to help young people be able to balance offline interactions with online interactions.